Enhanced piezoresponse of electrospun PVDF mats with a touch of nickel chloride hexahydrate salt - Dhakras, Dipti; Borkar, Vivek; Ogale, Satishchandra; Jog, Jyoti Prakash (Nanoscale, 2012)
PVDF nanofibers are prepared using electrospinning. The effect of addition of a hydrated salt, nickel chloride hexahydrate (NiCl2 center dot 6H(2)O), on the phase formation is examined. Addition of the hydrated salt (NC) is found to enhance the polar beta phase by about 30%. The peak to peak piezo-voltage generated for PVDF NC is almost 0.762 V, a factor of 3 higher than that for PVDF. The fiber mats exhibit a significantly enhanced dynamic strain sensor response. The voltage generated per unit micro-strain developed during the free vibration test for PVDF was 0.119 mV whereas it was 0.548 mV for PVDF NC, exhibiting a non-linearly enhanced performance vis a vis the increase in the beta phase component.